2019
DOI: 10.31372/20190402.1033
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self-perceived and Clinically Diagnosed Gingival Status among 12–15-year-old Children in Indonesia

Abstract: A few studies have revealed the self-perceived gingival status using questionnaires among children. Perceived health is a crucial factor that has an impact on quality of life. The objective of the study was to assess self-perceived and clinically diagnosed gingival status among children in Indonesia. This was a cross-sectional study of 494 schoolchildren (aged 12–15 years). Periodontal status was recorded using the gingival index (GI) and plaque index (PI) based on the World Health Organization standards. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…However, sensitivity and specificity are often inversely related [25]. The results of the present study are similar to a previous study conducted in Jakarta, Indonesia, where the specificity of selfreported condition was higher than sensitivity [7,19]. A screening indicator-such as self-reported presence of caries, fillings, or tooth loss-is desired to have high sensitivity [25] which is not the case for the three indicators in this study.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, sensitivity and specificity are often inversely related [25]. The results of the present study are similar to a previous study conducted in Jakarta, Indonesia, where the specificity of selfreported condition was higher than sensitivity [7,19]. A screening indicator-such as self-reported presence of caries, fillings, or tooth loss-is desired to have high sensitivity [25] which is not the case for the three indicators in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Individual perception of oral health involves a comprehensive understanding of oral disease, tissue damage, altered functional ability, pain, and aesthetics as part of psychological and psychosocial aspects [6]. Previous studies have shown that the validity of selfreported oral health can vary from promising to questionable depending on the assessed condition, tools, setting and population [1][2][3][4][5][6][7][8][9]. Self-reported use of dentures and number of teeth present in the oral cavity had good validity while reporting the presence of gingivitis and oral hygiene status had poor validity [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large population in Indonesia, epidemiological studies on the oral health status of children have been limited [15,16,17,18]. As the capital of Indonesia, Jakarta was considered a reference for other major cities in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…World Health Organization (WHO) guidelines have recommended that an epidemiological survey should assess the oral health status of school children at 12 years of age [12], as all permanent teeth, except for third molars, should have erupted by this age [13,14]. However, little attention has been paid to the oral health status of children in Indonesia, on which there is limited data available in the literature [15,16,17,18]. Based on the background detailed above, the aims of this study were to assess dental caries and the erosive tooth wear status of 12-year-old children in Jakarta, Indonesia and to investigate the risk factors associated with dental caries and erosive tooth wear in these children.…”
Section: Introductionmentioning
confidence: 99%